Efek Pemberian Ekstrak Daun Lidah Buaya (Aloe Vera) Terhadap Penyembuhan Luka Bakar Tikus Putih Jantan (Rattus Novergicus) Galur Wistar - Simbolon, Boyke Marthin; Hutasoit, Maria Angelina Br; Tarigan , Elviyanti Br (Syntax Corporation, 2026)
Burn injuries are a major cause of morbidity and mortality worldwide, accounting for approximately 180,000 deaths annually. Conventional treatments for burns often cause side effects such as allergic reactions and antibiotic resistance. Aloe vera has been traditionally used as a natural remedy for burns due to its bioactive compounds. This study aims to investigate the effect of aloe vera leaf extract administration on burn wound healing in male Wistar rats (Rattus norvegicus). This experimental research employs a post-test only control group design with 12 rats divided into four groups: negative control, positive control (silver sulfadiazine), and two treatment groups receiving different doses of aloe vera extract. Second-degree burns were induced using a heated iron plate. Parameters observed include wound diameter, healing time, and histopathological analysis of skin tissue. Aloe vera leaf extract contains bioactive compounds such as vitamins A, C, E, flavonoids, saponins, and tannins that play roles in wound healing through anti-inflammatory, antibacterial activities, and collagen synthesis stimulation. This research is expected to provide scientific evidence regarding the effectiveness of aloe vera as a safe, affordable, and accessible natural treatment alternative for burns in the community.